h - Chambers, Samuel Allen, 1972- (Oxford : Oxford University Press, 2013)
What if 'liberal democracy' were a contradiction in terms? This text distinguishes liberalism (a logic of order) from democracy (a principle of disordering) to defend a Rancierean vision of impure politics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: x; Political science -- Philosophy; Liberalism; Democracy